2007
DOI: 10.1007/s11060-007-9373-8
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective analysis of the efficacy and tolerability of levetiracetam in patients with metastatic brain tumors

Abstract: Seizures are a common complication of metastatic brain tumors (MBT), affecting approximately 27-50% of all patients during the course of their illness. Treatment of tumor-induced seizures is often inadequate with traditional antiepileptic drugs (AED) due to a variety of factors, including activation of glutamatergic NMDA receptors, alterations of neuronal input pathways, and tumor growth. Levetiracetam (LEV) is a 2nd generation non-enzyme inducing AED with a novel mechanism of action, binding to neuronal synap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(15 citation statements)
references
References 28 publications
0
14
0
1
Order By: Relevance
“…In a uncontrolled prospective study, LEV was shown to be well tolerated and provided a good seizure improvement in 17 patients with BTE (Usery, Michael et al, 2009). Further studies confirmed the good profile of LEV in BTE Rosati, Buttolo et al ;Maschio, Albani et al 2006;Newton, Goldlust et al 2006) and metastatic brain tumor epilepsy Newton, Dalton et al 2007). Several experts recommend use of LEV as first monotherapy in BTE Vecht and Wilms ;Vecht and van Breemen 2006;van Breemen, Rijsman et al 2009), although others still suggest valproic acid, lamotrigine and topiramate as first choice treatments (van Breemen, Wilms et al 2007).…”
Section: -5 Antiepileptic Pharmacotherapymentioning
confidence: 61%
“…In a uncontrolled prospective study, LEV was shown to be well tolerated and provided a good seizure improvement in 17 patients with BTE (Usery, Michael et al, 2009). Further studies confirmed the good profile of LEV in BTE Rosati, Buttolo et al ;Maschio, Albani et al 2006;Newton, Goldlust et al 2006) and metastatic brain tumor epilepsy Newton, Dalton et al 2007). Several experts recommend use of LEV as first monotherapy in BTE Vecht and Wilms ;Vecht and van Breemen 2006;van Breemen, Rijsman et al 2009), although others still suggest valproic acid, lamotrigine and topiramate as first choice treatments (van Breemen, Wilms et al 2007).…”
Section: -5 Antiepileptic Pharmacotherapymentioning
confidence: 61%
“…TAS are partially controlled with multiple and high doses of antiepileptic drugs [1] such as acetazolamide, phenobarbital, valproic acid, perampanel, zonisamide, gabapentin and levetiracetam [2,3]. Concerning metastatic tumors, treatment of levetiracetam reduced seizure frequency to more than 50% in all 13 patients [4]. Similar results were obtained from the use of valproic acid.…”
Section: Introductionmentioning
confidence: 79%
“…Meanwhile, evidence continues to mount documenting both the effectiveness and safety of newer-generation AEDS, like levetiracetam, oxcarbazepine and pregabalin [152,[196][197][198][199][200][201][202][203][204]. Though direct comparisons against the older drugs are generally lacking, theoretical advantages include the lack of any effect on cytochrome P450, and the fact that these drugs generally target specific risk factors for tumour-induced seizures [81].…”
Section: Aeds For Seizure Controlmentioning
confidence: 99%